Cross-Talking of Pathway-Specific Regulators in Glycopeptide Antibiotics (Teicoplanin and A40926) Production - Andrés Andreo-Vidal; Oleksandr Yushchuk; Flavia Marinelli; Elisa Binda (Antibiotics, 2023)
Teicoplanin and A40926 (natural precursor of dalbavancin) are clinically relevant glycopeptide antibiotics (GPAs) produced by Actinoplanes teichomyceticus NRRL B-16726 and Nonomuraea gerenzanensis ATCC 39727. Their biosynthetic enzymes are coded within large biosynthetic gene clusters (BGCs), named tei for teicoplanin and dbv for A40926, whose expression is strictly regulated by pathway-specific transcriptional regulators (PSRs), coded by cluster-situated regulatory genes (CSRGs). Herein, we investigated the “cross-talk” between the CSRGs from tei and dbv, through the analysis of GPA production levels in A. teichomyceticus and N. gerenzanensis strains, with knockouts of CSRGs cross-complemented by the expression of heterologous CSRGs. We demonstrated that Tei15* and Dbv4 StrR-like PSRs, although orthologous, were not completely interchangeable: tei15* and dbv4 were only partially able or unable to cross-complement N. gerenzanensis knocked out in dbv4 and A. teichomyceticus knocked out in tei15*, implying that the DNA-binding properties of these PSRs are more different in vivo than it was believed before. At the same time, the unrelated LuxR-like PSRs Tei16* and Dbv3 were able to cross-complement corresponding N. gerenzanensis knocked out in dbv3 and A. teichomyceticus knocked out in tei16*. Moreover, the heterologous expression of dbv3 in A. teichomyceticus led to a significant increase in teicoplanin production. Although the molecular background of these events merits further investigations, our results contribute to a deeper understanding of GPA biosynthesis regulation and offer novel biotechnological tools to improve their production.